Dialog dengan yang tak Terlihat: Menguak Pesan Penglihatan Elifas dalam Ayub 4:12-17 - Sonata, Valeria (Sekolah Tinggi Teologi Torsina Surakarta, 2024)
This study examines Eliphaz's vision in Job 4:12-17, which has given rise to various interpretations regarding the identity of the spirit that appears. Through textual analysis, it is found that Eliphaz’s message, accusing Job of sin and doubting his righteousness before God, contradicts the depiction of Job as a righteous man in the book’s prologue. Although initial attempts to shake Job’s faith through physical and emotional suffering prove ineffective, Satan’s message of unbelief reappears through the vision Eliphaz recounts, indicating a thematic continuation of skepticism surrounding the authenticity of human righteousness and devotion to God. The study also explores the complexities of the language and theological context surrounding the vision and the implications of the influence of an evil spirit that may have played a role in conveying this misleading message. Abstrak Penelitian ini membahas visi Elifas dalam Kitab Ayub 4:12-17, yang menimbulkan berbagai interpretasi mengenai identitas roh yang muncul. Melalui analisis teks, ditemukan bahwa pesan Elifas, yang menuduh Ayub berdosa dan meragukan kebenarannya di hadapan Tuhan, bertentangan dengan penggambaran Ayub sebagai orang benar dalam prolog kitab. Meskipun upaya awal untuk menggoyahkan iman Ayub melalui penderitaan fisik dan emosional terbukti tidak berhasil, pesan ketidakpercayaan Setan muncul kembali melalui penglihatan yang diceritakan Elifas, yang menunjukkan kelanjutan tematik dari skeptisisme seputar keaslian kebenaran manusia dan pengabdian kepada Tuhan. Penelitian ini juga mengeksplorasi kompleksitas bahasa dan konteks teologis yang mengelilingi visi tersebut, serta implikasi dari pengaruh roh jahat yang mungkin berperan dalam penyampaian pesan yang menyesatkan ini.